FROM EMPOWERMENT TO DEPENDENCY: EXAMINING THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON COMMUNITY INDEPENDENCE - Dadan Ramdhan; Amirah Azzahra; Muhammad Rafi Thoriq (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze corporate social responsibility (CSR) implementation motives and their implications for community self-reliance. The study employed a qualitative approach with a literature review method, analyzing scientific articles, sustainability reports, and CSR-related regulations. The results indicate that CSR implementation is influenced by three primary motives: regulatory compliance, corporate image building, and business interests through the creating shared value (CSV) approach. Although CSR contributes to improving community well-being, its impact on self-reliance remains limited. This is due to the dominance of aid-based approaches, low community participation, and a program orientation that emphasizes the legitimacy and strategic interests of the company over capacity building. As a result, CSR tends to produce dependency and pseudo-impact, where improvements in well-being are not accompanied by sustainable improvements in community capacity. Therefore, the effectiveness of CSR in promoting self-reliance depends heavily on participatory program design, based on local needs, and oriented toward long-term capacity building.